2021
DOI: 10.3390/foods10092167
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tremella as Fat Substitute for the Enhancement of Physicochemical and Sensory Profiles of Pork Sausage

Abstract: Pork fat in sausage was replaced by tremella at different proportions during the process, and the physicochemical and sensory profiles of pork sausage were evaluated. Five recipes with the replacement proportion of 0%, 25%, 50%, 75%, and 100% tremella were manufactured, and their proximate compositions, water activities, textures, colors, water holding capacities (WHC), and amino acid compositions were investigated. The results showed that the protein, ash and moisture content, lightness, redness, and WHC of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The texture is a crucial aspect of the sensory experience of T. fuciformis , and over-processing could result in the heavy loss of its flavor [ 7 , 26 ]. The effects of different blanching methods on the textural properties of T. fuciformis were shown in Figure 1 and Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The texture is a crucial aspect of the sensory experience of T. fuciformis , and over-processing could result in the heavy loss of its flavor [ 7 , 26 ]. The effects of different blanching methods on the textural properties of T. fuciformis were shown in Figure 1 and Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…T. fuciformis can improve the sensory attributes and physicochemical properties of foods, often as a meat substitute or fat substitute and also as a supplement to bread [ 6 ]. Hu [ 7 ] et al used T. fuciformis to replace 75% of the pork fat in pork sausages and found that the pork sausages had the best organoleptic properties. Lin [ 8 ] et al added T. fuciformis polysaccharides (TFPS) to low-fat yogurt, which increased the solids content and water-holding capacity of the yogurt, and had positive effects on sensory and texture.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al (2019) found that the incorporation of curdlan increased the L * value and decreased the a * value of frankfurter sausages, which is in accordance with the results of the present study. This phenomenon could be explained that the color of pork batter gel was affected by the own color of ASK gum (Hu et al, 2021). Moreover, the L * value of gel‐style meat products is closely associated with the water in the gel, which could be attributed to the enhanced light reflection by trapping more water in the gel network structure, contributing to higher L * values (Grossi, Søltoft‐Jensen, Knudsen, Christensen, & Orlien, 2012; Zhao et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Each sample was compressed twice to achieve the force-time curve. Then, hardness, springiness, gumminess, and cohesion force were obtained [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%